Comparative Antiviral Efficacy of Generic Sofosbuvir versus Brand Name Sofosbuvir with Ribavirin for the Treatment of Hepatitis C - Tang, L.; Kamat, M.; Shukla, A.; Vora, M.; Kalal, C.; Kottilil, S.; Shah, S. (Interdisciplinary Perspectives on Infectious Diseases, 2018)
Background. Chronic hepatitis C infection is a major cause for liver failure and liver cancer and can be treated with highly effective all oral directly acting antiviral (DAA) drugs. Generic versions of these DAAs are available in India. Method. This was an open-label, single-center, prospective, nonrandomized observational study for the comparative safety and efficacy of generic versus brand name sofosbuvir with ribavirin therapy for chronic hepatitis C infection (all genotypes). Between December 2014 and December 2015, 66 patients received either generic sofosbuvir (400mg) or brand name SOLVALDI (400mg) with weight based ribavirin for 24 weeks in a single multispecialty hospital in Mumbai. Monitoring viral loads and safety labs was performed as per national guidelines. Results. Sustained virologic response was 72.4% versus 75.7% (p=0.78) among patients treated with generics and SOVALDI, respectively. At 4 weeks on-treatment, approximately 90% of patients from both groups had undetectable or below the lower limit of quantification. Change in hemoglobin was comparable in both groups (p=0.26). Conclusion. Generic versions of sofosbuvir reported in this study are safe and efficacious to treat hepatitis C. However, bioequivalency studies of all generic DAAs need to be performed before wider use of such drugs for the treatment of hepatitis C.